Between ethos and practice: are Ireland's new multi-denominational primary schools equal and inclusive?. Issue 4 (4th July 2019) - Faas, Daniel; Smith, Aimee; Darmody, Merike
Abstract: This article explores the ethos of multi-denominational primary schools in the context of increasing cultural and religious diversity in the Republic of Ireland. In particular, it investigates how the official ethos is played out in day-to-day school interactions. The mixed-methods study draws on data collected from 11 community national schools focussing on the perspectives of principals, teachers and pupils. The data indicates while schools' formal ethos sets out guiding principles and standards, a closer look reveals the specific identity of each individual school within the broader formal framework. The article presents a new perspective on school ethos research by exploring the extent to which it guides the promotion of diversity and tolerance in a multi-faith context. While the study is carried out in Ireland, it is also of interest to other jurisdictions where schools are faced with increasing religious diversity among their student population.